Digital Financial Inclusion, Financial Literacy, and Entrepreneurial Survival The Mediating Role of Digital Finance - Angguliyah Rizqi Amaliyah (Journal of Economic Education and Entrepreneurship Studies, 2026)
This study examines the impact of digital financial inclusion and financial literacy on entrepreneurial survival by considering the mediating role of digital finance. This issue is particularly relevant as the failure rate of micro, small, and medium enterprises (MSMEs) in Indonesia remains relatively high due to limited access to financing, low financial literacy, and disparities in digital technology adoption. Unlike most previous studies that primarily focus on direct relationships or macro-level impacts of digital financial inclusion, this study investigates the mediating mechanism of digital finance in the relationship between digital financial inclusion, financial literacy, and entrepreneurial survival at the micro-enterprise level. The study employs a quantitative approach using survey data collected from 150 entrepreneurs in Indonesia. The data were analyzed using path analysis and the Sobel mediation test to examine both direct and indirect effects among variables. The findings reveal that digital financial inclusion and financial literacy have a positive and significant effect on entrepreneurial survival. Furthermore, digital finance is proven to significantly mediate the relationship between these variables and business survival. These results provide empirical evidence that the utilization of digital financial services acts as a critical mechanism linking financial access and financial capability to business sustainability. The study contributes to the literature by highlighting the strategic role of digital finance in strengthening entrepreneurial resilience in the digital economy.